Molecular characterisation of two Ornithodoros savignyi enzyme isoforms belonging to the 5'-nucleotidase family - Neitz, A.W.H. (Albert Walter Herman) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.